Nonequilibrium molecular dynamics - Hoover, Wm.G.; Hoover, C.G. (Condensed Matter Physics, 2005)
Nonequilibrium Molecular Dynamics is a powerful simulation tool. Like its
equilibrium cousin, nonequilibrium molecular dynamics is based on timereversible
equations of motion. But unlike conventional mechanics, nonequilibrium
molecular dynamics provides a consistent microscopic basis for the
irreversible macroscopic Second Law of Thermodynamics. We recall here
how fast computers led to the development of nonequilibrium molecular dynamics
from the statistical mechanics of the 1950s. Computer-based theories
facilitated revolutionary breakthroughs in understanding during the
1970s and 1980s. The new idea key to the nonequilibrium development
was the replacement of the external thermodynamic environment by internal
control variables. The new variables can control temperature, or pressure,
or energy, or stress, or heat flux. These thermostat, barostat, ergostat,
... variables can control and maintain nonequilibrium states. We illustrate
the methods with a simple example well-suited to student exploration,
a thermostatted harmonic oscillator exposed to a temperature gradient. Нерівноважна молекулярна динаміка є потужним комп’ютерним
методом. Подібно до рівноважної, нерівноважна молекулярна динаміка базується на часово-зворотніх рівняннях руху. Але, на відміну
від звичайної динаміки, нерівноважна молекулярна динаміка містить узгоджений мікроскопічний базис для незворотнього макроскопічного другого закону термодинаміки. Ми показуємо тут,
як швидкодіючі комп’ютери приводять до розвитку нерівноважної
молекулярної динаміки на основі статистичної механіки 1950-х. Теорії, що базується на застосуванні комп’ютерів, сприяли
революційному прориву в розумінні протягом 1970-х, 1980-х. Новою
ключовою ідеєю для нерівноважного розвитку було заміщення зовнішнього термодинамічного середовища на внутрішні контролюючі змінні. Нові змінні можуть контролювати температуру або тиск,
енергію, напруження або тепловий потік. Такі термостатичні, баростатичні, ергостатичні,... змінні можуть контролювати і підтримувати
нерівноважні стани. Для ілюстрації ми використовуємо термостатичний гармонічний осцилятор, який піддається дії температурного
градієнта.